Crosstalk and microlens study in a color CMOS image sensor. - Agranov, G. (IEEE Transactions on electron devices)
The paper describes results of crosstalk investigations and microlens (μ-lens) scan experiments in a color CMOS image sensor with active pixel structure . The investigation of optical and electrical crosstalk was made on 7.8- and 5.6-μm pixels by using samples with continuous shift of color filter (CF ) and μ-lens across the array. As a result of this investigation, the distribution of sensitivity inside a pixel has been determined. By using minimum crosstalk criteria, the optimum parameters of the μ-lens manufacturing process and optimum position of the μ-lens was determined. The paper presents color maps of pixel sensitivity and crosstalk criteria as well as snapshots illustrating sensitivity distribution and collection area. The paper presents spectral characteristics measured at different relative apertures (f-number) as well. The quantitative analysis of spectral responses allowed us to determine the contribution of each component to the overall crosstalk.